The Effect of Doubled Concentration of Nanoparticles with Gamma-Rays Energy as Simulation Radiotherapy in Lung Cancer - Shihab Ahmed Jasim1, Nihad A. Saleh2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Nanoparticles are considered main mediatorss to improve the efficacy of radiotherapy. By their nano size, they can penetrate the cellular environment and concentrate inside it. Nanoparticles own high cross-section and energy mass attenuation coefficient which means that they have high energy absorption. This study focused on decreasing the irradiation dose required to kill malignant cells by direct injection of NPs inside tumor cells in order to increase the amount of absorbed dose by adding a doubled increased concentration of (zinc and tellurium) NPs in tumor cells with minimum injury to the surrounding healthy tissue and increasing the number of destroyed cancer cells. Method: The theoretical basis for conducting current study was that to increase organ tolerance for radiation dose absorption, the injected particles inside the tumor should have high radiation dose absorption inside tumor. Results: There was increasing apoptosis of cancer cells and decreasing malignant cells survivor in low dose in comparison with high dose without NPs. The number of dead cancerous cells was increasing with doubling increase of NPs which depends on cross-section that is usually depending on high mass energy absorption coefficient and type and amount of energy. Conclusion: Zinc and tellurium nanoparticles can potentiate the effect of radiotherapy on lung tumor cells through increasing number of destroyed malignant cells which depended on atomic number and cross-section.